‘We’re doing everything but treaty’: Law Reform and Sovereign Refusal in the Colonial Debtscape - Maria Giannacopoulos (Law Text Culture, 2023)
This article is the text of the John Barry Memorial Lecture in Criminology delivered at the University of Melbourne just four days after the unsuccessful Voice referendum and eleven days after the genocide in Gaza began to be unleashed. Following artists Matt Chun and James Tylor’s strikethrough of A̶u̶s̶t̶r̶a̶l̶i̶a̶ and extending this to the description of colonial l̶a̶w̶, colonial law in the place known as A̶u̶s̶t̶r̶a̶l̶i̶a̶ is revealed as sitting in a violent relation of domination toward Indigenous laws, peoples, lands, and languages that pre-existed it. L̶a̶w̶ and l̶a̶w̶s̶ imposed upon Aboriginal Land are usurpatory and as such form a nomopoly which in turn function to naturalize and then retrospectively legitimize the theft of Aboriginal land. This, it is argued is the work of the debtscape where legal apparatuses are on a reformist loop, working ceaselessly to cover over the fact of unpaid colonial debts as the foundation and enabling condition for A̶u̶s̶t̶r̶a̶l̶i̶a̶. Reckoning with unpaid sovereign debt is a form of decolonisation that is yet to come.